EFFECT OF RESISTANCE EXERCISES ON HANDGRIP STRENGTH IN POSTMENOPAUSAL WOMEN WITH OSTEOPENIA/OSTEOPOROSIS - HOLUBIAC I. Ș; GROSU V. T. (Editura Universitatii Transilvania din Brasov, 2020)
The present study aimed to verify the effects of a 12 months resistance training using the Bulgarian method by contrast (6 reps x 70% of 1RM + 6 reps x 50% of 1 RM) on handgrip strength in women with postmenopausal osteopenia/osteoporosis. Ten women with postmenopausal osteopenia/osteoporosis (over 50 years old) were distributed into two groups: exercise group (EX) (n = 5) and control group (C) (n = 5). Handgrip strength were measured before and at the end of the study using hydraulic hand dynamometer. Exercise group (EX) showed an increase by 12% at the end of the study for the dominant hand (p = .039) and by 10.53% for the nondominant hand (p = .041). The control group showed a decrease in handgrip strength by -2.14% for the dominant hand (p = .018) and by -3.65% for the non-dominant hand (p = .038).